Influence of subclinical infection by agents of tick fever in milking dairy cows Influencia de la infección subclínica por agentes de la fiebre por garrapatas en vacas lecheras - Pazinato R.* (2016)
Objective. The objective of this study was to evaluate the effect of subclinical infection by agents of tick fever in dairy cattle on milk parameters, such as production, composition, and quality. Materials and methods. The study was conducted in a private farm with 75 free-stall-housed dairy cows, from which 37 were evaluated. Monthly, individual milk samples were collected for compositional (fat, lactose, protein, and total solids) and quality (somatic cell counts (SCC) analyses. In addition, blood samples were collected in order to identify cows that were tick fever-negative and positive by PCR for one or more of the following etiological agents: Babesia bovis, Babesia bigemina and Anaplasma marginale. Results. The results showed increased SCC in positive animals for at least one of the agents when compared to non-infected cows (p<0.05). Milk production was significantly lower in A. marginale positive animals (p<0.05). An increase of about 40% in milk solids content was found in B. bovis positive cows. Also, an increment of approximately 23% in lactose was found on cows positives for B. bigemina. Conclusions. We may conclude that the presence of at least one of these parasites in dairy cattle affects composition or quality of their milk.